The Analysis of the Students' Characteristic to Achieve Differentiated Learning in English at the Eighth Grade of SMP Negeri 1 alasa - Hulu, Friska Juliani; Harefa, Afore Tahir; Daeli, Hidayati; Telaumbanua, Kristof Martin Efori (Universitas Nurul Jadid, 2025)
Differentiated learning is Learning that facilitates and recognizes student diversity in learning, according to students' readiness, interests and learning characteristics. Differentiated learning has elements that support/facilitate the diversity of student characteristics. Student characteristics reflect patterns of behavior and abilities resulting from innate and social environments so that they determine the pattern of activity. The objectives of the research are to analyze the students characteristics to achieve differentiated learning in English at the Eight Grade of SMP Negeri 1 Alasa in 2024/2025. The research type is a descriptive method with a qualitative approach. The subjects of this research are students' characteristics to achieve differentiated learning in English at the eighth grade.The results of the research show that students have a diversity of characteristics in learning. The diversity of student characteristics can be the basis for implementing differentiated learning. The application of differentiated learning that is tailored to the learning characteristics of students' learning styles is an effective strategy to improve students' collaboration skills in learning English.